Analysis of the Influence of Information Flow Topology in Platoon Applications - Freitas, Arthur D. M.; Coelho, Francisco J. S.; Campelo, Divanilson R.; Silva-Filho, Abel G. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2023: Anais do XLI Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2023.542, 2023)
In a vehicle platoon, the Information Flow Topology consists of the structure and organization of the communication network that interconnects the vehicles. When there is a high Frame Error Rate in the communication network, the vehicle platoon can become unstable and put drivers and passengers at risk. This work investigates the influence of the Information Flow Topology on a platoon in scenarios with different speeds, acceleration and deceleration amplitude, and levels of packet loss. Simulation results demonstrated that the Predecessor Follower topology can maintain safety and a more accurate intervehicular distance even in nonideal vehicular communication scenarios.